Jayaashree Industries: Revolutionising sanitary pad use in India - NARASIMHALU, Arcot Desai (Institutional Knowledge at Singapore Management University, 2012)
Arunachalam Muruganantham is a social entrepreneur dedicated to solving India’s menstrual health problems. He developed an unprecedented product as a solution: a low-cost, locally produced sanitary pad. In a paragon effort of frugal innovation, he reverse-engineered the industrial processes used to make sanitary-pads. The result was a small-scale, low-cost machine that could manufacture quality pads sold at a retail price 20% lower than the cheapest mass-produced brands. However, no one bought his pads until his wife began to sell them. After which, the two were unable to keep up with demand. This triggered his realization concerning the importance of including women as stakeholders in the operation. His next step was to figure out a way to increase the availability and access of the pads. He needed an innovative, bottom-of-the-pyramid solution and wanted to create a positive social impact along the entire value chain.